2015
DOI: 10.1162/rest_a_00460
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Training on Productivity and Wages: Firm-Level Evidence

Abstract: The Impact of Training on Productivity and Wages: Firm Level Evidence This paper uses firm level panel data of firm provided training to estimate its impact on productivity and wages. To this end the strategy proposed by Ackerberg, Caves and Frazer (2006) for estimating production functions to control for the endogeneity of input factors and training is applied. The productivity premium for a trained worker is estimated at 23%, while the wage premium of training is estimated at 12%. Our results give support to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(57 citation statements)
references
References 29 publications
5
49
2
1
Order By: Relevance
“…4 We also looked at literature that tries to factor in the cost of training (direct costs, forgone earnings and opportunity costs) to determine returns. Carefully designed literature that treats for selection issues suggests that OJT is linked with wage and productivity gains, but with firms benefiting more than workers (Almeida and de Faria 2014;Dearden, Reed, and Van Reenen 2006;and Konings and Vanormelingen 2015). (See Section 2.1 for a detailed review.…”
Section: Summary Of Results By Key Questionsmentioning
confidence: 99%
See 3 more Smart Citations
“…4 We also looked at literature that tries to factor in the cost of training (direct costs, forgone earnings and opportunity costs) to determine returns. Carefully designed literature that treats for selection issues suggests that OJT is linked with wage and productivity gains, but with firms benefiting more than workers (Almeida and de Faria 2014;Dearden, Reed, and Van Reenen 2006;and Konings and Vanormelingen 2015). (See Section 2.1 for a detailed review.…”
Section: Summary Of Results By Key Questionsmentioning
confidence: 99%
“…However, we cannot do this practically without running into serious methodological challenges. Directionally, however, there is evidence of rather modest returns to ALMPs (Betcherman, Dar and Olivas 2004), whereas the returns to OJT have been found to be higher (Konings and Vanormelingen 2015). However, the challenge is that we are not able to attribute causality to program design properly as these programs target different groups of trainees.…”
Section: At Current Employer: Effect On Productivity Wages and Costsmentioning
confidence: 98%
See 2 more Smart Citations
“…In samples of workers of all ages, studies have found that on-the-job training is linked to higher employee productivity (Barrett & O'Connell 2001;Bartel 1995;Conti 2005;Konings & Vanormelingen 2009;Zwick 2006), slower depreciation of human capital (Groot & Maassen van den Brink 2000;Neuman & Weiss 1995), future employability (Crépon, Ferracci, & Fougére 2007;Lechner, Miquel, & Wunsch 2005) and wage growth (Bartel 1995;Dearden, Reed, & Van Reenen 2006;Groot 1999). However older employees have fewer remaining years of work to reap the returns on their training investment (Ben-Porath 1967).…”
Section: A Possible Mechanism: Training and Wagesmentioning
confidence: 99%